2009
DOI: 10.1007/bf03173475
|View full text |Cite
|
Sign up to set email alerts
|

Emergent literacy and learning to write: A predictive model for italian language

Abstract: The aim of the present study is twofold: (1) contribute to identifying a model for the variables that compose the emergent literacy construct and their relationships; (2) assess the predictive power of the emergent literacy model on early writing abilities in a transparent orthography language.We examined emergent literacy skills in 464 children (mean age 5.5, range: 48-6.1) who were followed longitudinally until entering the 1st grade in primary school. Exploratory and Confirmatory factor analyses were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 25 publications
0
47
0
7
Order By: Relevance
“…That spelling results to be the common core between reading and writing confirms at the formal literacy level the existence of a common predictive core among emergent literacy skills. Past research has showed that kindergarteners' conceptual knowledge of the writing system, as assessed by an invented spelling task, predicts both, writing (Pinto, Bigozzi, Accorti Gamannossi, & Vezzani, 2009) and reading performances in primary school (Bigozzi et al, 2014), thus contributing to our knowledge on the similarities or differences in cognitive basis of reading and spelling. In a transparent writing system, children learn the sound to sign correspondences and how to process them fluently quite early, in first grade.…”
Section: Stability Of Reading and Writing Parameters At Two Points Inmentioning
confidence: 99%
“…That spelling results to be the common core between reading and writing confirms at the formal literacy level the existence of a common predictive core among emergent literacy skills. Past research has showed that kindergarteners' conceptual knowledge of the writing system, as assessed by an invented spelling task, predicts both, writing (Pinto, Bigozzi, Accorti Gamannossi, & Vezzani, 2009) and reading performances in primary school (Bigozzi et al, 2014), thus contributing to our knowledge on the similarities or differences in cognitive basis of reading and spelling. In a transparent writing system, children learn the sound to sign correspondences and how to process them fluently quite early, in first grade.…”
Section: Stability Of Reading and Writing Parameters At Two Points Inmentioning
confidence: 99%
“…Oral narrative competence. Narrative competence was assessed via a narrative production task (Pinto, Bigozzi, Accorti Gamannossi, & Vezzani, 2009;Spinillo & Pinto, 1994) in which children were asked to tell a narrative. In Italian kindergarten and primary schools, students receive instruction in the production of fictional stories, which is a common school practice.…”
Section: Materials and Measuresmentioning
confidence: 99%
“…Written narrative competence. Narrative competence was assessed via a narrative production test (Pinto et al, 2009;Spinillo & Pinto, 1994). The children were instructed to write a narrative of their choice and were allowed a maximum of 60 min; all the children completed the task within 30-50 min.…”
Section: Materials and Measuresmentioning
confidence: 99%
“…Story structure coding (fromPinto, Bigozzi, Accorti Gamannossi, & Vezzani, 2009). Simple descriptions of actions without characteristics of narrative style, such as conventionalized story opening or closing.…”
mentioning
confidence: 99%